Analysis of Trends in Young Entrepreneurial Initiative in Romania in the Context of Contemporary Challenges and European Development - Beatrice TROCINESCU; Flavia BOGOEVICI; Cristian CARAIANI; Silviu Mihai DRAGOMIR (Revista de Management Comparat International)
This study analyses the trends among young people with entrepreneurial initiative in Romania, in the context of current economic and social challenges, as well as the processes of European integration and development. The research aims to identify the motivations, obstacles, and opportunities faced by Romanian youth with entrepreneurial intentions, highlighting the role of education, digitalization, and state support in shaping the entrepreneurial journey. Data was collected through a questionnaire administered to a sample of 76 young Romanians aged between 18 and 35. The results show that the desire for financial independence and the need for selffulfilment are the main drivers of entrepreneurial initiative. The lack of financial resources, fear of failure, political instability, and economic uncertainties are perceived as significant barriers. At the same time, digitalization is seen as a key factor in increasing business competitiveness, and government programs such as Start-up Nation are perceived as necessary support among young people. This paper offers a fresh perspective on how Romanian youth with entrepreneurial initiative perceive the current business environment, with its opportunities and threats, outlining concrete directions for improving the local entrepreneurial ecosystem.